The Public Administration's responsibility for damages arising from bullyng and cyberbullyng at school - Carmen Delgado Moral (ADIDE Federación, 2017)
In this article I am dealing with the study of the responsibility of educational institutions in cases of bullying and cyberbullying. Through a legal and jurisprudential analysis of some conflicts we are looking into this current problem because, although it has existed for a long time, today it has become more serious perhaps due to an increase of the violence in the present society. Bullying and cyberbullying are a difficult but priority problem for some centers because of the social and health consequences for the victims; Therefore, we will reflect on the preventive and protective function that the centers must do to avoid this type of situation, as well as the role of the educational inspection, as guarantor of the rights of the users of this public service, in the monitoring of the protocols Which must be applied against any violation of student rights.